Evaluating the Role of Cytokine Receptor-like Factor 2 and Janus Kinase 2 in Adult Acute Lymphoblastic Leukemia - Hassan, Naglaa M.; El Ashry, Mona S.; Abdellateif, Mona; Hassan, Reem Nabil (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of the present study was to assess the diagnostic, prognostic, and predictive roles of the cytokine receptor-like factor 2 (CRLF2) and the Janus Kinase 2 (JAK2) genes expression in adult acute lymphoblastic leukemia (ALL) patients. METHODS: The expression levels of CRLF2 and JAK2 genes were evaluated in the bone marrow (BM) samples of 105 adult ALL patients, compared to 12 healthy controls. The data were correlated to the patients’ relevant clinic-pathological features, response to treatment and survival rates. RESULTS: There was a significant overexpression of JAK2 in ALL patients compared to the control group [0.04 (0–160.8) and 0.006 (0–0.009), respectively, p < 0.001]. Similarly, CRLF2 was overexpressed in ALL patients in comparison to control subjects [0.008 (0–78.2) and 0.0005 (0–0.006), respectively, p < 0.001]. The sensitivity, specificity, and the area under curve (AUC) for JAK2 were 78.1%, 81.8%, and 0.796, respectively (p < 0.001), and that of CRLF2 were 92.4%, 90.9%, 0.958, respectively (p < 0.001). When combining both JAK2 and CRLF2 for the diagnosis of ALL patients, it revealed 90.9% sensitivity, 91.4% specificity, and AUC of 0.957 (p < 0.001). The JAK2, CRLF2, or their combined expression associated significantly with the increased expression of MHC-II (p = 0.015, 0.001, and 0.004, respectively). However, they had no significant impact on patients’ response to treatment, overall (OS), and disease-free survival (DFS) rates (p > 0.05 for all). CONCLUSION: JAK2 and CRLF2 could be a potential useful diagnostic molecular marker for ALL patients, which allow them to be successful targets for ALL therapy.